PENGARUH PENDEKATAN DEEP LEARNING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS III MATA PELAJARAN IPAS SD NEGERI SAPEN - Asri Nurrohmah, Ayuna; Tukiyo; Zudhah Ferryka, Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the deep learning approach on the learning motivation of third-grade students in the IPAS subject at Sapen Public Elementary School. This study employed a descriptive quantitative method with a sample of 21 students. The data collection techniques used included observation, questionnaires, and documentation. The research instrument consisted of a learning motivation questionnaire that had been tested for validity and reliability. The validity test results showed a percentage of 92% in the “highly valid” category, while the reliability test yielded a Cronbach’s Alpha value of 0.867, indicating that the instrument is reliable. Data analysis was conducted using SPSS version 27, involving normality tests, homogeneity tests, and hypothesis testing via the independent samples t-test. The results of the normality test showed that the data were normally distributed with a significance value of 0.683 for the experimental class and 0.261 for the control class. The results of the homogeneity test showed a significance value of 0.364 > 0.05, so the data were declared homogeneous. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, so H0 was rejected and H1 was accepted. The results of the study indicate that the deep learning approach has a positive impact on students’ motivation to learn. Students become more active, enthusiastic, and engaged in the IPAS learning process. Thus, the deep learning approach can be used as an effective alternative teaching method to enhance the motivation of elementary school students to learn.